The role of social support and emotional exhaustion in the association between work-family conflict and anxiety symptoms among female medical staff: a moderated mediation model - Hui Zhang; Leiwen Tang; ZhiHong Ye; Ping Zou; Jing Shao; Man Wu; Qi Zhang; Guojin Qiao; Shaoyu Mu (BMC Psychiatry, 2020)
Abstract Background Limited work has been done to explain how work-family conflict is related to anxiety symptoms and the roles of emotional exhaustion and social support may play. Methods Based on a sample of 764 female nurses and physicians, a model was tested in which emotional exhaustion served as a mediator and social support was regarded as a moderator between work-family conflict and anxiety symptoms. Results This current study supported a moderated mediation model where the relationship between work-family conflict and anxiety symptoms via emotional exhaustion was weakest for female medical staff who reported high levels of social support. Conclusions This study contribute to providing an understanding of how and when work-family conflict affects anxiety symptoms. The results implicate a wide range of interventions aimed at promoting mental wellbeing among female medical staff for policymakers and individuals.